       Re: Evaluating a sum from terms generated by the Array

• To: mathgroup at smc.vnet.net
• Subject: [mg109519] Re: Evaluating a sum from terms generated by the Array
• From: Bob Hanlon <hanlonr at cox.net>
• Date: Mon, 3 May 2010 06:11:31 -0400 (EDT)

```Array[((-1)^(# + 1) (x)^#)/#! &, 3, 1] // Total

x^3/6 - x^2/2 + x

Plus @@ Array[((-1)^(# + 1) (x)^#)/#! &, 3, 1]

x^3/6 - x^2/2 + x

Sum[(-1)^(n + 1) x^n/n!, {n, 3}]

x^3/6 - x^2/2 + x

Series[1 - E^-x, {x, 0, 3}] // Normal

x^3/6 - x^2/2 + x

% == %% == %%% == %%%%

True

Bob Hanlon

---- davef <davidfrick2003 at yahoo.com> wrote:

=============
I want to evaluate a sum from a series I created using the Array
function.

For example; I specify

Array[((-1)^(# + 1) (x)^#)/# ! &, 3, 1 ]

which gives me the following 3 terms of output:

{x, -(x^2/2), x^3/6}

Can anyone tell if and how I can turn these 3 terms into a sum to be
evaluated?

```

• Prev by Date: Re: Evaluating a sum from terms generated by the Array function
• Next by Date: space between Output cels
• Previous by thread: Re: Evaluating a sum from terms generated by the Array
• Next by thread: Re: Evaluating a sum from terms generated by the Array